A Semantic Graph-Based Japanese Vocabulary Learning Game - Ratsameetip Wita (2018)
© 2018, Springer International Publishing AG, part of Springer Nature. Study foreign languages in college level are sometimes offered as an academic minor. To achieve an academic minor, students have to enroll in selected subjects in specific field. Studying Japanese as an academic minor are offered at Chiang Mai University. The minor degree requires student to pass four classes of basic Japanese grammars and vocabulary including hiragana, katakana and kanji. The Japanese minor degree are designed for (more or less) equivalent to N5 level in Japanese Language Proficiency Test (JLPT). In this work, Vocabulary matching game is developed to assist student vocabulary learning process. The game was designed as multi-stages, automatic generated MCQ game based on progression of the courses including matching between Japanese-Romanji, Japanese-Thai and Thai-Japanese. Vocabulary Semantic graph and frequently mistaken words were used to generate the question stem and plausible distractors using collaborative filtering technique.